Impact of Migrant Remittances on Economic Empowerment of Women: A Macroeconomic Investigation - Ibourk, Aomar; Amaghouss, Jabrane (International Journal of Economics and Financial Issues, 2014)
The present research has the ambition to contribute to the literature by providing a better visibility on the impact that remittances can generate in the level of women remained in the country, both in terms of economic activity and the status of women in households. To this end, this work mobilizes macroeconomic aggregate data to verify the impact of remittances on women activity at the international level. This work involves the macroeconomic data of a sample of 58 countries observed from 1999 to 2010. The results of the macroeconomic approach are substantially different when going from one region to another. In particular, the presented estimates show that the effect of transfers on female labor supply depends on the studied area. The complexity of the studied phenomenon shows the existence of contradictory effects, in which case the local and regional characteristics may play an important role. Keywords: remittances; economic empowerment; women; migration JEL Classifications: C13; F22; O11